Structural and functional properties of ozone-treated quinoa starch - Ramos, Giselle Vallim Corrêa; Branco, Ivanise Guilherme [UNESP]; da Matta Junior, Manoel Divino; Ferreira, Julieta Adriana; Ditchfield, Cynthia; Sobral, Paulo José do Amaral; Moraes, Izabel Cristina Freitas (Elsevier, 2024)
Ozone is a very powerful oxidizing agent and can rapidly decompose without generating waste. Ozone was applied to oxidize quinoa starch suspensions (10 g/100 g) were subjected to oxidation by ozonization and the effect of ozone generation time (OGT: 10, 20 and 30 min) was investigated on their structural and functional properties. As OGT increased from 10 to 30 min, amylose content and relative crystallinity reduced. Gel-permeation chromatography analysis indicated amylose depolymerization and structural analysis by FTIR revealed that ozonized starches had a considerable reduction in the degree of crystallinity with increasing OGT. Carbonyl/carboxyl group contents, paste clarity (26 %), oil absorption capacity (23 %) and peak apparent viscosity, values increased significantly (p ≤ 0.05) for treated samples. Ozone increased the mean diameter (D [2,3]), the onset temperature (DSC), and pasting properties. Thus, ozonization is a powerful method to modify starch, as well as a safe and inexpensive oxidizing process.
Keywords: Chenopodium quinoa; Ozonization; Starch oxidation